Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.7759/cureus.37023
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating ChatGPT's Ability to Solve Higher-Order Questions on the Competency-Based Medical Education Curriculum in Medical Biochemistry

Abstract: BackgroundHealthcare-related artificial intelligence (AI) is developing. The capacity of the system to carry out sophisticated cognitive processes, such as problem-solving, decision-making, reasoning, and perceiving, is referred to as higher cognitive thinking in AI. This kind of thinking requires more than just processing facts; it also entails comprehending and working with abstract ideas, evaluating and applying data relevant to the context, and producing new insights based on prior learning and experience.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…[ 8 ] Previous studies have proven its capacity to solve cases and complex questions in various domains. [ 9 10 ] Chatbots can help in both generating the cases and also provide solution to the cases. For example, AI-based chatbots could be developed that can provide students with immediate feedback on their responses to case scenarios based on AETCOM competencies.…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] Previous studies have proven its capacity to solve cases and complex questions in various domains. [ 9 10 ] Chatbots can help in both generating the cases and also provide solution to the cases. For example, AI-based chatbots could be developed that can provide students with immediate feedback on their responses to case scenarios based on AETCOM competencies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies conducted by medical professionals in India have shown that the ChatGPT is a reliable tool for solving problems that require higher-level thinking, interpretation, analysis, evaluation, or formulation of opinions and predictions based on evidence in pathology, biochemistry, and microbiology [8][9][10]. In addition, ChatGPT was proficient in answering straightforward queries seeking factual information in microbiology [8].…”
Section: Discussionmentioning
confidence: 99%
“…, ChatGPT software has been successfully used to pass the ( ) Basic Life Support ( ) test [ 27 ] and the Plastic Surgery In-Training Exam (PSITE) [ 28 ]. ChatGPT has produced good outcomes in surgical education and training while resolving more complex medical biochemistry-related issues [ 30 ]. These findings demonstrate that ChatGPT’s knowledge is suitable for teaching foundational courses.…”
Section: The Impact and Research Progress Of Chatgpt On Medical Educa...mentioning
confidence: 99%